Why Butterflies Don't Leave - Spatial development of new firms - Erik Stam (European Regional Science Association (ERSA), 2005)
There is an emerging interest in the local conditions of entrepreneurship and firm dynamics. The often-cited examples of entrepreneurship in successful regional clusters show that entrepreneurship is really a localized phenomenon, which seems to be at odds with the increased globalization of economic activity, in which firms are said to be relatively footloose and easily become multinational enterprises. Other authors have noted that in spite of information and communication technologies, the vital importance of face-to-face contact cannot be discounted (Hallowell, 1999); as Leamer and Storper (2001: 641) observe, the Internet "allows long distance 'conversations' but not 'handshakes' ”. Next to controversies concerning the role of the global and the local for firms (cf. West, 2002), there is a general weakness in the theory of the firm concerning the analysis of (new) firm dynamics. According to Geroski (2001) the theory of the firm in economics is preoccupied by the question of why firms exist, and it is both very narrow and very static. Further work in this area might be usefully extended to address the question of how firms grow and develop over time, and this, in turn, will force people to think through issues associated with what makes change difficult for firms. We will deal with these issues in a discussion of evolutionary theories of the firm in general, and specific theories of the entrepreneurial firm and the multinational firm in particular, and regional cluster approaches. The central question in this paper is: "Are there necessary interactions between the development of entrepreneurial firms and their spatial organization over time?”. We will deal with this question in a longitudinal way, i.e. analyze the development of entrepreneurial firms and the changes in their spatial organization during their life course. The development of entrepreneurial firms involves the firm–founding (Shane and Khurana, 2003) and the subsequent early growth (Garnsey, 1998) of the firm. These firms are not self-employed (anymore), and mostly not (yet) a multinational corporation; in a sense they are neither small nor large, but dynamic, turning from a caterpillar into a butterfly (cf. Penrose 1995), and are central to dynamics in the new, or entrepreneurial economy (Bresnahan et al., 2001; Audretsch and Thurik, 2003). The empirical part of this study is based on comparative case studies (Eisenhardt, 1989; Yin, 2003) of 25 entrepreneurial firms, and 8 micro firms in four propulsive industries, namely professional business services, biomedicals, graphics-media, and shipbuilding. The spatial organization of firms consists of the dynamic constructs of locational adjustment and locational flexibility, which refer to the adjustment of the spatial organization of firms outside the headquarter (the location at which the entrepreneur/owner-manager executes his activities) of the firm and to the flexibility of the location of the headquarter respectively. With these two dimensions the tendency towards concentration or dispersion of the firm can be observed (cf. Storper, 1997, p.299-300). The spatial development of new firms consists of the sequence of locational events. Locational events refer to the changes in the state of the spatial organization of firms. The different types of locational events were coded in order to find typical sequences of locational events (cf. Abbott, 1995). Concrete events have been studied that may be unique to some extent. However, "[t]he focus is not on how or why something happened but on how or why something happens” (Mohr, 1982, p.5). We are looking for mechanisms that explain the spatial development of new firms. The abstract knowledge resulting from insight into these mechanisms may be more generally applicable. We have used a combination of quantitative and qualitative methods. We registered the general characteristics of the entrepreneur, his network relations, the firm (its strategy, structure and capabilities), inter-organizational relations, and their locations. The qualitative method involved a life history of the firm as told by the entrepreneur (Van Geenhuizen et al., 1992). This life history has been explicated with a critical incident technique (Tjosvold and Weicker, 1993; Chell and Pittaway, 1998). The fieldwork involved the study of how (location) decisions are actually made during the life course of emerging firms and how they affect and are affected by the firms' development in general. Next to the quantitative data derived from the interviews other data from company archives, the press and other media was collected. The empirical study shows that capabilities more often seem to constrain (as a place-specific sunk cost) than to enable the spatial flexibility of entrepreneurial firms. However, certain organizational capabilities have to be built in order to become multilocational, especially on the interregional and international levels. The inter-organizational networks in regional clusters are hardly relevant in the explanation of the dynamics in the spatial organization of entrepreneurial firms. They only seem to constrain the location behavior in the early phases of entrepreneurial firms, when radical changes in the spatial organization are almost never considered at all.
Keywords: 330